A canção como instrumento para o letramento lírico - Andrade, Alexsandra Dantas Oliveira (2015)
This paper presents a proposal to the lyrical genre teaching in the 7th year of Elementary Education Major. It shows the place of poetry, that is, as the lyric text can contribute to the formation of readers and the lyrical literacy. The proposal contemplates the use of songs of Brazilian Popular Music (MPB) to work lyrical resources. It is a multimodal proposal that brings the songs to go beyond the presentation of theories, becoming a tool to achieve the desire to hear good music, to seek the understanding and interpretation of the letters and identify literary devices present in the MPB songs. All this associated with the use of new Information and Communication Technologies (ICT) as a means for realization of this project. This work has a rich theoretical contribution of Octavio Paz, Salvatore D'Onofrio, Rildo Cosson, Antonio Candido, Anazildo Vasconcelos da Silva, Manoel Reis, Sylvia Helena Cyntrão, Antonio Carlos Xavier, Sánchez Miguel etc.